Fact-checking linguistic technologies in information genres of modern mass media - Shevchenko , Larysa; Dergach, Dmytro (Current issues of Ukrainian linguistics: theory and practice, 2024)
The authors systematically analyzes the linguistic technologies of fact-checking (as countermeasures to disinformation and fakes), that aresynchronized with the stylistic nature of modern mass media information genres. According to their functional and communicative heterogeneity, the principles of fact-checking in traditional and new media are distinguished in the article. It is noted that in the information genres of traditional media (in newspaper, magazine, television, radio discourses) fact-checking is associated with the editorial policy of the mass media, the professional activities of certified journalists, that are controled by the current legislation on information. It was determined that new media, systematically represented by forms of virtual communication, often don’t mention the category of the author, violate the linear model of informing, relying on the communicative effects of sensationalism, primacy, shock, which as a result generate ambiguity and cognitive dissonance in the perception of information content. Research attention is paid to the semiotic heterogeneity of informational texts and contexts, which complements and diversifies their functional and stylistic resource and potential, focusing on additional markers that are fundamentally important, in particular, for fact-checking. The authors also comment on the thesis regarding the correct understanding of the semantic organization of informational media messages, which depends on the background knowledge of the recipients. This makes it possible to determine the conceptually important task of the author of information content – taking into account commented criteria of a high-quality, reliable information message, to actualize on its basis the perception of objective reality by the mass audience, which will model the further interpretation of the fact. In this case, it is also mentioned about social responsibility: not only of the authors of media texts and contexts, but also the recipients who implement secondary reflection on them. The conclusion states that the efficiency of prospectively effective algorithms of information fact-checking in modern mass media can positively influence the quality of the relevant content, which affects the language consciousness of the recipients. And as a result, it actualizes the communicative resource, the stylistic dominants of media information genres as an important and convincing source of information about objective reality, which forms perceptions and values, and therefore determines the prospects for the development of modern society.